EXAMINATION OF FUNCTIONAL MOVEMENT STATUS, INJURY HISTORY AND SPECIFIC MOTOR PERFORMANCE AMONG YOUNG ELITE FOOTBALL PLAYERS - Pucsok, József Márton; Szentes-Szendrey, Anna; Balogh, László; Tarnóczy, Zalán (Stadium - Hungarian Journal of Sport Sciences, 2023)
Purpose: The primary aim of this study was to find any relationship between total and selected FMS scores, recent (within two years) injury status, and specific motor performance. The secondary purpose of the study was to examine, wheather is there any relationship between injuries of the hamstring muscle and injuries of the hip and knee joints of the body.Material and methods: Youth and junior football players were volunteered to take part in our examination. A total of 45 subjects participated in our study, their age varied from 16 to 19. We implemented a five to one scoring system to identify the status of injuries. Finally, a complete FMS testing and a single leg (unilateral) standing long jump test were performed, involving all participants.Beside evaluating the total FMS scores of the participants, we chose to specifically stress on five test batteries out of seven. Out of the five tests we further focused on three FMS tests.Results and conclusion: In this given population, we have not found significant relationship  between total FMS scores and overall scores (5 to 1) of injury status. Our results also did not indicate any significant correlation between selected FMS scores and single leg standing long jump performance.